An investigation of the effects of self-reported self-control strength on shooting performance. (January 2021) - Englert, Chris; Dziuba, Anna; Wolff, Wanja; Giboin, Louis-solal
Abstract: During professional shooting tournaments, which typically last multiple hours, athletes must stay focused at all times in order to perform at their highest levels. Sustaining attention over extended periods of time relies on self-control. Crucially, perceived state self-control strength appears to wane as a function of task duration, which ultimately can impair shooting performance. In the present study, we tested the assumption that the level of self-reported self-control strength decreases over the course of a 1-h shooting task measured twice during a regular training day and separated by a 2-h break. Additionally, we assumed that shooting performance would be linked with fluctuations in self-control. A total of 21 shooters (14 elite and 7 sub-elite) took part in this study and were asked to perform a series of 10 shots at a standardized target, five times in the morning and five times in the afternoon (i.e., 100 shots total). The participants also reported their perceived state self-control strength at the baseline (prior to the start of the morning session as well as the afternoon session) and after a series of 10 shots each in the morning and afternoon (i.e., 12 measurements in total). In line with our hypotheses, we observed that perceived state self-control diminished with the number of shots performed, and that perceived state self-control could explain shooting performance. Additionally, these observations could explain the difference in shooting performance between elite and sub-elite athletes. The results suggest that the perception of self-control strength is highly important for optimal shooting performance. Practical implications are discussed. Highlights: Shooting performance deteriorates over time. Perceived state self-control decreases during shooting competition. Reduced state self-control precedes impaired shooting performance. Elite shooters display higher and more robust state self-control than sub-elites.